The Use of STEM-Based Virtual Laboratory (PhET) of Newton’s Law to Improve Students’ Problem Solving Skills - Siti Ichliyalatul Laila; Mita Anggaryani (Universitas Muhammadiyah Makassar, 2021)
Problem-solving is one of the skills that must be mastered in the 21st century. The objective of this research is to describe the practicality of using a STEM-based virtual laboratory in distance learning (online) to practice problem-solving skills in the subject of Newton's Law. This study's subjects were three classes totalling 102 students of SMA Negeri 1 Cerme Gresik. Employing an experimental design, this research used observation, questionnaires, and tests (pre-test and post-test) as the data collection methods. To analyse the data, several tests (homogeneity test, normality test, gain test, t-test, and effectiveness) were used. The results showed that the mean score of the pre-test was 54.57 and that of post-test was 81.13. This indicates that the students’ learning outcomes have increased by 26.38, with the average size of the gain test classified in the medium criteria, namely 0.58 or 58%. The result of this study contributes to the development of online-based learning strategies during the covid-19 pandemic. In brief, the use of STEM-based Virtual Laboratory (PhET) has significant effects on students’ problem- solving skills. STEM-based Virtual Laboratory was quite effective for teaching Newton’s Law in the platform of online learning.